Application of ILs as carbonate scales dissolver - Muhammad Suhaimi, Man; Hanida, Abdul Aziz; Syamsul B., Abdullah (Elsevier B.V., 2022)
The scale formation was a crucial problem in the petroleum industry. Among the scales, calcium carbonate (CaCO3) was the predominant scale produced. Thus, a suitable alternative solution is needed to be identified to overcome the effect of hydrochloric acid (HCl), which is usually used to dissolve CaCO3. This study introduced ionic liquid (ILs) for scales dissolver due to their unique properties, likely known as a green solvent. This ILs N-pyridinium chloride ([NPy][Cl]) was studied experimentally in order to know the performance during the dissolution of scale toward some parameters. The parameters tested in this study are carbonates scales, the concentration of ILs, stirring speed, pH and temperatures. In order to get better efficiency of the performance on actual condition, [NPy][Cl] was tested with model crude oil, salinity, corrosion evaluation and regeneration of the used ILs. The finding shows that the [Npy][Cl] is suitable for replacing HCl as a carbonate scale dissolver due to its ability to dissolve carbonate scales. Furthermore, the performance of [NPy][Cl] in the dissolution rate of carbonate scales was maintained, although inaccurate condition testing. This finding will enhance crude oil production by using solvent-based ILs in this application.